2022
DOI: 10.1186/s12885-022-09439-x
|View full text |Cite
|
Sign up to set email alerts
|

Utility of prognostic nutritional index and systemic immune-inflammation index in oral cancer treatment

Abstract: Purpose This study aimed to evaluate the utility of inflammation-based prognostic scores (IBPS) and systemic immune-inflammation index (SII) in the treatment of oral cancer patients. Methods For the 183 patients enrolled in this study, IBPS and SII were calculated from peripheral blood samples obtained before and after treatment and at the time of relapse. We examined overall survival (OS) and disease-free survival (DFS) using previously reported c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 42 publications
1
42
0
Order By: Relevance
“…SII can serve as a valuable index for predicting the clinical outcomes of human diseases, especially cancers [31][32][33]. High SII is associated with the poor prognosis of several types of cancer, such as bladder cancer [31], cervical cancer [34], oral cancer [35], gastric cancer [36], and breast cancer [36]. In the current study, for the first time, we found that high SII is an independent risk factor of OLF and that SII is positively associated with OLF score.…”
Section: Discussionmentioning
confidence: 99%
“…SII can serve as a valuable index for predicting the clinical outcomes of human diseases, especially cancers [31][32][33]. High SII is associated with the poor prognosis of several types of cancer, such as bladder cancer [31], cervical cancer [34], oral cancer [35], gastric cancer [36], and breast cancer [36]. In the current study, for the first time, we found that high SII is an independent risk factor of OLF and that SII is positively associated with OLF score.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the neutrophil to lymphocyte ratio (NLR), 10 platelet to lymphocyte ratio (PLR) 11 were closely related to thromboembolic incidents in cancer patients. The systemic immune-inflammation index (SII), 12 and prognosis nutritional index (PNI), 13 as novel inflammatory markers, accurately represent the body’s inflammatory response, but their efficacy for the diagnosis of tumor-associated VTE remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the identification of sensitive and specific inflammatory biomarkers for AF among the stroke patients further guides individualized therapy and achieves the goal of precision medicine [ 18 ]. SIII and SIRI can reflect the systemic inflammatory activity of the body, and they have great potential in predicting the prognosis of cancer patients [ 19 21 ]. Higher monocyte and neutrophil counts and lower lymphocyte counts have been associated with a higher CVD risk [ 22 24 ].…”
Section: Discussionmentioning
confidence: 99%